2022
DOI: 10.1111/jfbc.14346
|View full text |Cite
|
Sign up to set email alerts
|

Salmon sperm DNA prevents acute liver injury by regulating alcohol‐induced steatosis and restores chronic hepatosis via alleviating inflammation and apoptosis

Abstract: Current medications used to treat alcoholic liver injury (ALD) can cause secondary damage to the liver. Therefore, it is important to improve alcoholic liver injury from the perspective of dietary and nutritional supplementation. Nucleic acids, as functional biomolecules, are present in almost all foods, especially in aquatic products, but their edible research has been neglected for a long time. Hence, the effects of a typical aquatic nucleic acid, namely, salmon sperm DNA, in acute, and chronic alcoholic liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…During acute alcoholic liver injury, alcohol induces excessive production of reactive oxygen species (ROS), leading to elevated levels of liver lipids [ 22 , 23 ], oxidative stress [ 24 ], and release of inflammatory cytokines including TNF-α, IL-6, and IL-1β [ 25 ], thereby exacerbating inflammation [ 26 ]. In this study, we observed that RDAE mitigated alcohol-induced weight loss and attenuated the increase in liver index.…”
Section: Discussionmentioning
confidence: 99%
“…During acute alcoholic liver injury, alcohol induces excessive production of reactive oxygen species (ROS), leading to elevated levels of liver lipids [ 22 , 23 ], oxidative stress [ 24 ], and release of inflammatory cytokines including TNF-α, IL-6, and IL-1β [ 25 ], thereby exacerbating inflammation [ 26 ]. In this study, we observed that RDAE mitigated alcohol-induced weight loss and attenuated the increase in liver index.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary nucleic acids have been found to have various physiological effects in vivo , other than being recycled through the salvage pathway. Their effects have attracted attention, and the physiological effects of dietary nucleic acids reported so far include the maintenance of immune responses [ 1 3 ], suppression of inflammation in adipose tissue [ 4 ], improvement of glucose tolerance [ 4 ], and protection of liver function [ 5 , 26 ]. In this study, we discovered that dietary nucleic acids and guanosine have an inhibitory effect on cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…As a mechanism of action, experiments using hepatocytes have shown that deoxyadenosine in salmon milt extract may suppress liver inflammation [49]. On the other hand, salmon sperm DNA has also been reported to prevent liver inflammation [50,51]. DNA-Na supplementation significantly suppressed increases in CtsB and IL-1β mRNA associated with stress-induced hippocampal inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%